Diabetic nephropathy and its risk factors in a society with a type 2 diabetes epidemic: a Saudi National Diabetes Registry-based study. - Khalid Al-Rubeaan (Public Library of Science (PLoS), 2014)
Aims The prevalence of diabetic nephropathy and its risk factors have not been studied in a society known to have diabetes epidemic like Saudi Arabia. Using a large data base registry will provide a better understanding and accurate assessment of this chronic complication and its related risk factors. Methodology A total of 54,670 patients with type 2 diabetes aged ≥ 25 years were selected from the Saudi National Diabetes Registry (SNDR) and analyzed for the presence of diabetic nephropathy. The American Diabetes Association (ADA) criterion was used to identify cases with microalbuminuria, macroalbuminuria and end stage renal disease (ESRD) for prevalence estimation and risk factor assessment. Results The overall prevalence of diabetic nephropathy was 10.8%, divided into 1.2% microalbuminuria, 8.1%macroalbuninuria and 1.5% ESRD. Age and diabetes duration as important risk factors have a strong impact on the prevalence of diabetic nephropathy, ranging from 3.7% in patients aged 25-44 years and a duration of >5 years, to 21.8% in patients ≥ 65 years with a diabetes duration of ≥ 15 years. Diabetes duration, retinopathy, neuropathy, hypertension, age >45 years, hyperlipidemia, male gender, smoking, and chronologically, poor glycemic control has a significantly high risk for diabetic nephropathy. Conclusion The prevalence of diabetic nephropathy is underestimated as a result of a shortage of screening programs. Risk factors related to diabetic nephropathy in this society are similar to other societies. There is thus an urgent need for screening and prevention programs for diabetic nephropathy among the Saudi population.